2006
DOI: 10.1021/la060390o
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-Modulated Phase Separation in Lipid Bilayer Membranes

Abstract: Cellular membranes exhibit a variety of controlled curvatures, with filopodia, microvilli, and mitotic cleavage furrows being only a few of many examples. Coupling between local curvature and chemical composition in membranes could provide a means of mechanically controlling the spatial organization of membrane components. Although this concept has surfaced repeatedly over the years, controlled experimental investigations have proven elusive. Here, we introduce an experimental platform, in which microfabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
263
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(283 citation statements)
references
References 36 publications
19
263
1
Order By: Relevance
“…Other researchers have examined the role of membrane curvature in the segregation of pre-existing phases. 14,30,31 They found that stiffer, ordered-phase domains segregate to regions of lower curvature. This minimizes the net bending energy of the system.…”
Section: Adhesion Induces the Formation Of An Ordered Phasementioning
confidence: 99%
“…Other researchers have examined the role of membrane curvature in the segregation of pre-existing phases. 14,30,31 They found that stiffer, ordered-phase domains segregate to regions of lower curvature. This minimizes the net bending energy of the system.…”
Section: Adhesion Induces the Formation Of An Ordered Phasementioning
confidence: 99%
“…Such deformation helps to reduce the length of the phase boundary, and thus the energy of line tension (Baumgart et al 2003). Once the membrane is deformed, the induction of curvature by the bound virus and AB5 toxin can further enhance phase separation, which may act as a feedback loop (Parthasarathy et al 2006).…”
Section: Induction Of Curvaturementioning
confidence: 99%
“…It is clear from the images, the PSDs, the cross-correlation analysis, and the intensity contour plots that the replica does not pattern the phase separation of the membrane. It might be possible that there are differences at the nanoscale regarding the contours of the lipid bilayers and the substrates, but it is unlikely to be a main factor given the many papers that report lipid bilayers follow faithfully the topography of even highly rough silica substrates [15][16][17] . We thus conclude that the gross topography of the glycan network alone cannot pattern domains in multiphase membranes.…”
Section: Controls For Gross Topographic Effectsmentioning
confidence: 99%
“…Indeed, while there are many reports of lipid membranes supported on non-biological polymers such as polyethylene glycol, polyacrylamide or polyethyleneimine [17][18][19][20] which seek to mitigate non-'equilibrium' behaviour, such systems have been used mainly to study the effects of polymer hydration 21 on the mobility of lipids 18,19 , or to preserve the function of transmembrane protein inclusions 17,22 . Furthermore, while it is widely acknowledged that a greater understanding of parameters that influence the size and length-scale of membrane domains is required [6][7][8][9][10][11][12][13]23,24 , as far as we know, systematic studies exploring the effects of biopolymers (the subject of this letter), or other more commonly used polymers in the field [17][18][19][20] on the phase behaviour of lipid membranes have not been conducted. To investigate the possible effects of biologically relevant polymers on the behaviour of membranes, we designed an in vitro solid-supported experimental platform that allows, through fluorescent labelling and confocal microscopy, the study of lipid membranes interacting with hydrated networks of glycans with arbitrary glycan composition and variable network configurations.…”
mentioning
confidence: 99%